Comparative analysis of tissue damage and inflammatory response for transoral laser microsurgery versus open surgery in the management of early-stage laryngeal cancer - Jingchun Ge; Jiawei Gui; Hui Xiao (Discover Oncology)
Abstract Objective This study aimed to analyze the perioperative dynamic changes of tissue damage and inflammatory response markers, and to determine whether these differ between transoral laser microsurgery (TLM) and open surgery (OS) in early-stage laryngeal cancer. Methods In a randomized controlled study conducted at the 2nd Affiliated Hospital of Harbin Medical University, four hundred patients with early-stage laryngeal cancer were randomly assigned to undergo either TLM (n = 200) or OS (n = 200) treatment. Blood samples were collected at various time points: upon admission, immediately before surgery, 2 h post-surgery, 24 h post-surgery, 48 h post-surgery, and one-week post-surgery. These samples were analyzed for a range of biomarkers indicative of inflammatory processes and tissue damage, including high-sensitivity C-reactive protein (hs-CRP), white blood cell count (WBC), platelet count, interleukin-6 (IL-6), cortisol, creatine kinase (CK), and tumor necrosis factor-alpha (TNF-α). The analysis of these markers aimed to provide insights into the physiological responses and potential tissue-level changes in the study participants. Additionally, surgical information, perioperative complications, and 2-year postoperative follow-up Overall Survival were meticulously recorded and analyzed. Results There were no significant differences in baseline characteristics between the two groups. Analysis of clinical and perioperative data revealed that patients who underwent TLM experienced shorter operating times, reduced hospital stays, and lower estimated blood loss and Visual Analog Scale (VAS) scores compared to those in the OS group. Additionally, the rates of general anesthesia, as well as complications such as hemorrhage and infection, were lower in the TLM group. Postoperative measurements indicated that hs-CRP, WBC, IL-6, and cortisol levels were significantly lower in the TLM group at several time points. However, there was no difference in the two-year Overall Survival between the two groups. Conclusion This study demonstrated that in early-stage laryngeal cancer, TLM treatment results in a reduced inflammatory response, less tissue damage, and lower stress levels, as indicated by decreased levels of hs-CRP, IL-6, and cortisol, compared to OS treatment. These findings suggest that TLM has the potential to facilitate a quicker recovery and improve patient-reported outcomes compared to OS.